Cell Homing - The New Age Therapy in Regenerative Endodontics - Bharadwaj , R Sumukh; Shivakumar , Ashwini Tumkur; Kalgeri , Sowmya Halasabalu; Choudhary , Adarsh; Prajwal M S ,; Gowda , Supreeth S (Cell Homing - The New Age Therapy in Regenerative Endodontics, 2024)
Root canal therapy or apexification is the standard treatment for teeth that are irreversibly diseased or necrotic. By attempting to repair the injured "pulp-like" tissue, regenerative endodontics can prevent necrosis and maintain the vitality of the teeth. The main clinical benefit is the development of root. The term "pulp-like" tissue does not relate to pulp-dentin complex development or regenerated pulp tissue with an odontoblastic layer. The ability of endogenous stem cells to regenerate tissue is the foundation of the cell homing technology. The term "cell homing" describes the migration or infiltration of endogenous cells into the cite in response to physiological, biochemical, or biological stimuli, or through passive flow in the form of a blood clot from the apical tissue. The American Association of Endodontists has established its success criteria for Regenerative Endodontic Procedures. Despite difficulties, Heet al. (2017) found that cell homing is now the most clinically viable method for dental pulp regeneration. Future advancements in tissue engineering could lead to new scaffold designs, antibacterial protocols, and the use of other signalling molecules, improving the outcome's predictability. This review study aims to provide a summary of cell homing as well as a number of strategies for encouraging the regeneration of damaged pulp.